ID: 87: TRANSCRIPTION FACTOR CREB3L3 IS A NOVEL REGULATOR FOR ADIPOCYTE BIOLOGY AND METABOLISM. Issue 4 (22nd March 2016) - Duncan, S; McCann, M; Qiang, G; Gil, V; Whang Kong, H; Liew, C
Abstract : The presence of differential metabolic risks between the metabolically-protective subcutaneous adipose tissue (SAT) and the disease-associated visceral adipose tissue (VAT) is well established, but the mechanisms that cause these differences are not well understood. Cyclic AMP responsive element binding protein 3-like 3 (CREB3L3), a previously characterized liver-specific ER-bound transcription factor, was found to be expressed in murine SAT and VAT. In obese human subjects and an obese mouse model, we found that CREB3L3 is downregulated in SAT, but not in VAT. To examine the role of CREB3L3 in adipocyte biology and metabolism, we created a fat-specific CREB3L3 knockout (KO) mouse using the AdipoQ-Cre mouse. To establish a potential role for CREB3L3 in adipocytes, we examined in vitro differentiated adipocytes from isolated WT and KO primary stromal vascular fraction. We observed that ablation of CREB3L3 in SAT adipocytes significantly upregulated expression of both lipogenic and lipolytic markers. At the same time, we also observed significantly increased expression of thermogenic markers like PGC1α and Cox8b. Taken together our data suggest potential upregulation of the fat futile cycle in SAT upon deletion of CREB3L3. Surprisingly, we found that CREB3L3 KO tends to downregulate expression of markers of both lipogenesis and lipolysis in VAT adipocytes. This observation could potentially be contributed by the tendency of CREB3l3 KO VAT to have inhibited differentiation. To investigate the in vivo function of CREB3L3, we challenged WT and KO mice with high fat diet with weekly body weight assessment. We observed that CREB3L3 ablation in adipose tissues promotes significant weight gain in mice on HFD. Unexpectedly, despite being heavier, the KO mice are not more glucose intolerant or insulin resistant. These data together suggest that ablation of CREB3L3 could potentially promote fat storage in adipose tissues to prevent metabolic diseases caused by ectopic fat deposition.